Color and fluorescent imaging of t-BOC-protected quinizarin methacrylate polymers - Lee, CW; Yuan, ZZ; Ahn, KD; Lee, SH (AMER CHEMICAL SOC, 2002)
A polymerizable quinizarin (Qz) dye precursor having both methacrylate and tert-butoxycarbonyl (t-BOC) groups has been prepared and radically copolymerized to obtain mono-t-BOC-protected quinizarin polymers as fluorescent imaging materials. The mono-t-BOC-protected quinizarin methacylate 3 (t-BQzMA) is a unique monomer having an acid-labile t-BOC blocking group along with a polymerizable methacrylate group. The t-BOC-protected quinizarin polymers obtained by copolymerization of t-BQzMA with methyl methacrylate were readily modified to regenerate phenol groups by deprotection of t-BOC groups in the quinizarin moieties with photochemical treatment in the presence of a photoacid generator. The polymers rendered color and fluorescent imaging properties based on a photolithographic method: fluorescent images obtained without wet development and fluorescent relief patterns after wet development followed by flood exposure.
Keywords: CHEMICALLY AMPLIFIED RESISTS; FILMS